Alterações fisiológicas induzidas pelo ácido salicílico na germinação e crescimento de plantas de tomate em condições de restrição hídrica - Galviz Fajardo, Yutcelia Carolina (2019)
Water stress is the environmental factor that most affects plant development. Exogenous application of salicylic acid (SA) appears as a technique capable of improving plant tolerance to drought. The aim of this work was to evaluate the influence of this molecule on the physiological performance of tomato seeds and plants under water restriction. To this end, two experiments were conducted. The goal of the first study was to evaluate the effect of osmotic conditioning with different concentrations of AS (0.0; 25 and 50μM) on germination and growth of tomato plants at different levels of water retention capacity (WRC): 20; 30; 40 and 100%. Germination (%), first germination count (FGC%), germination rate index (GRI), length and dry mass of shoot and root (SL, RL, SDM and RDM) of the seedlings were evaluated, as well as the expression of enzymes that participate in metabolic processes during the germination and activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX). Lipid peroxidation and hydrogen peroxide content were also determined. The application of SA in drought conditions did not favor the germination and growth of the seedlings, inducing a higher SOD activity and lower lipid peroxidation, as well as a greater accumulation of hydrogen peroxide. However, under favorable water conditions, higher concentrations of SA favored germination speed and seedling growth. In the second experiment, the effect of seed conditioning and root application of SA on tomato plants was evaluated in a greenhouse. During the course of the assay, seeds were seeded in polystyrene seeds trays containing commercial substrate under optimal conditions of water availability, maintained in this condition for 21 days after emergence (DAE). After this period, seedlings were transferred to 700mL plastic pots, where at 28 DAE, WRC levels were established (20; 30; 40 and 100%). The growth of the plants was evaluated by shoot and root length and mass, foliar area and gas exchanges. In addition, the activity of antioxidant enzymes SOD, APX and CAT was quantified. The results indicate that water deficit significantly reduces growth, negatively affects photosynthetic parameters and decreases respiration activity. Although it induced variations in antioxidant system, neither of the two forms of SA application was able to promote improvements in morphological and physiological characteristics under water deficit. It can be conclude that the application of SA is not a viable alternative to reduce the effects of water deficit.